Pengembangan Augmented Reality Untuk Pengenalan Huruf Hijaiyah Bagi Anak Pra Sekolah - Kamal, Zuma Fahmi; Ikrimach, Ikrimach (Jutisi : Jurnal Ilmiah Teknik Informatika dan Sistem Informasi, 2023)
Understanding Hijaiyah letters is the first step in preparing to read the Qur'an, the holy book of Islam. For this reason, interesting learning is needed to increase interest in reading Hijaiyah letters during childhood. Choosing the right learning media method is very important. In this study, the focus is on the utilization of augmented reality technology is developed and able to provide an improved solution for Hijaiyah Letter Recognition with an Application that visualizes Hijaiyah letters into a 3D representation so that the visual appearance is more attractive. They apply a method called "marker based," which allows them to see these 3D letters in a real-world environment, making children able to see what 3D Hijaiyah letters objects they want. In this research, the examination of the app involved "blackbox" testing, revealing that all aspects of the application operated effectively and without issues on the whole. This application helps students easily personalize 3D objects of Hijaiyah Letters for Early Childhood, so that children can learn to recognize well and interactively.Keywords: Hijaiyah Letters; 3D Objects; Augmented Reality; AndroidÂ AbstrakAplikasi pengenalan huruf Hijaiyah merupakan solusi yang telah disusun dengan tujuan membantu individu, terutama anak-anak, untuk memahami dan menghafal huruf Arab yang digunakan dalam bahasa Arab dan dalam membaca Al-Quran. Dalam usaha meningkatkan efisiensi pembelajaran huruf Hijaiyah, teknologi Augmented Reality (AR) digunakan sebagai metode yang menciptakan pengalaman pembelajaran yang lebih interaktif dan menarik. penggunaan teknologi Augmented Reality dalam aplikasi pengenalan huruf Hijaiyah melibatkan perangkat berbasis smartphone atau tablet yang dilengkapi dengan kamera. Aplikasi ini memungkinkan pengguna untuk melihat huruf Hijaiyah di dunia nyata mereka dengan tambahan elemen visual dan interaktif yang memperkaya pengalaman belajar. Dalam studi ini, dilakukan pengujian "blackbox" yang menghasilkan temuan bahwa semua fitur aplikasi berfungsi dengan baik secara keseluruhan. Aplikasi ini membantu anak mempersonalisasi objek 3D dengan mudah Huruf Hijaiyah untuk Anak Usia Dini, sehingga kanak-kanak dapat belajar mengenal sacara baik dan interaktif.